User Satisfaction of Accessibility to Public Transportation - Abdul Rahman, Rima; Mohd Noor, Harifah; Imang, Ubong; Tartaglia, Mario (Environment-Behaviour Proceedings Journal, 2024)
This study evaluates user satisfaction with the bus in urban areas to improve public transportation services. Thus, bus facilities, bus accessibility, safety, and fare are critical dimensions for investigating user satisfaction when accessing buses in Kota Kinabalu, Sabah, Malaysia. A total of 450 questionnaires were collected using a descriptive design and quantitative approach. The results show that the factors that need to be emphasized are bus accessibility and public transport facility factors. This study assists transportation authorities in addressing low-satisfaction areas to improve bus services and enhance overall public transportation use.